Influence of employee resourcing on organizational performance of devolved governments in South Eastern Kenya region - Jonah, James M; Misango, Sedina B.; Ombuki, Charles (My University, 2019)
The study focused on the influence of human capital factors on performance of devolved Governments in South Eastern Kenya region. The specific objective of the study being to establish the influence of employee resourcing on organizational performance of the devolved governments in South Eastern Kenya region. The target population comprised county government of Kitui, Machakos and Makueni senior staff numbering 179 members. A sample size of 59 county officials was randomly selected using stratified simple random sampling techniques. The data was analysed by use of descriptive and inferential statistics. The findings of the study established that there was no statistically significant influence of employee resourcing on performance of Machakos and Makueni county governments. However, employee resourcing had a statistically significant influence on the performance of Kitui county government. The study recommends an improvement in the conduct of employee resourcing to include current trends that include use of softwares to track job applications, development of a mobile recruitment strategy, increase the focus on passive and potential candidates, and a growth in the emphasis for social networks
Keywords: Devolved Governments; Employee resourcing; Human capital; Organizational performance